Perception and treatment of melancholy in the writings of Hildegard of Bingen (c. 1098-1179) - Eglė Sakalauskaitë-Juodeikienë (Neurologijos seminarai)
Hildegard of Bingen (c. 1098-1179) was a medieval nun and an abbess, a mystic, a composer, a poet, an author of medical treatises, and one of the few women at the time who wrote both theological and scientific texts. In this paper, I analyze Hildegard’s book Liber subtilitatum diversarum naturarum creaturarum (Book of Subtleties of the Diverse Nature of Creatures), compiled around 1151-1158 and consisting of two books: Physica and Causae et curae. The aim of this study is to understand how the phenomenon of melancholy in its three meanings (as body fluid, character type, and a disease) was perceived by one of the brightest medieval thinkers. Even though Hildegard’s writings were influenced by deep knowledge of the Scripture, the abbess also accepted Greco-Roman medical system (classical humoral theory), astrology, medieval agricultural worldview, and the wisdom of folk medicine. Melancholy was interpreted in Hildegard’s medical texts as a heart and a brain disease which was caused by the overabundance of black bile produced in the spleen. The abbess recommended various medicinal herbs (fennel, mallow, primrose, rue, etc.) and substances of animal (ostrich, heron, ants) and mineral (onyx) origin in order to reduce excessive amount of black bile. Hildegard explained the mechanism of action of these medications using concepts of humoral theory, principle of contraria contrariis, as well as knowledge of medieval folk medicine and elements of religious and magical healing.